(3hOGYG ddgehe hGdGMRGfs (3YdGL eVGO ddbdb hGdGcJFGHs - (3GdYXe, YGHOI GdeDjOs ((3GdQjGVs (3OGQ GdCLjGd ddfTQs, 2005)
(3gPG GdOhGA echf ef ehGO WHjYjI (B100 %(3, JCKjQg SQjY, aYGd LOG, djSJ dg BKGQ LGfHjI, jSJeQ eaYhdg eG OGe GdYdGL efJXeG, jDNO YfO GdMGLg , jSJYed ddUZGQ h GdcHGQ(B. (3GdJQcjH (B: (3CjGJ bQBfjI, h CMGOjK fHhjI, h CbhGd deaSQjf KbGI eYJHQjf, h HYV GdJLGQH GdhGbYjI GdUGObIs
11
Keywords: (3GdGSdGe hYde GdfaSs